Identifikasi Kandungan Klorofil Daun dan Pengaruhnya terhadap Produksi Kopi Robusta (Coffea canephora) - Badiu, Rendri Al; ., Mawardi (Program Studi Agroteknologi, 2022)
Coffee in Indonesia. Robusta coffee (Coffea canephora) is a type of coffee that is well known in Indonesia. Each Robusta coffee clone has a different yield potential. The difference in production is related to plant metabolism, especially photosynthesis. The results of photosynthesis are influenced by various factors, both factors originating from within the plant and from outside. The main factor that is quite important in the process of photosynthesis of coffee plants is the content of chlorophyll in the leaves. Leaf chlorophyll content is one indicator of the photosynthetic capacity of coffee plants. Coffee clones that have a high chlorophyll content have a greater ability in the photosynthesis process. The increase in the rate of photosynthesis of plants will directly affect the amount of coffee production. Therefore, it is very important to identify the chlorophyll content of coffee leaves and their effect on coffee production. This study aims to identify differences in leaf chlorophyll content and its effect on the production of three robusta coffee clones. This research was conducted in Silo Village, Silo District, Jember Regency from April to July 2015. The study used a Completely Randomized Design (CRD) with 3 treatments with 6 replications. The treatments consisted of coffee clones BP 358, BP 409, and BP 936. The observed parameters were the content of chlorophyll a, chlorophyll b, and total chlorophyll and coffee production. The results showed that the average chlorophyll content of Robusta coffee leaf clone BP 936 was 523.23 mol/m2, clone BP 409 was 514.36 mol/m2, and BP 358 was 499.74 mol/m2. The chlorophyll content of clones BP 936 (523.23 mol/m2) and BP 409 (514.36 mol/m2) showed no significant difference and the production was 0.92 tons/ha and 0.97 tons/ha, respectively. while the leaf chlorophyll content of clone BP 358 was 499.74 mol/m2 with a production of 0.75 tons/ha.